2011
DOI: 10.26421/qic11.9-10-2
|View full text |Cite
|
Sign up to set email alerts
|

Crossovers induced by discrete-time quantum walks

Abstract: We consider crossovers with respect to the weak convergence theorems from a discrete-time quantum walk (DTQW). We show that a continuous-time quantum walk (CTQW) and discrete- and continuous-time random walks can be expressed as DTQWs in some limits. At first we generalize our previous study [Phys. Rev. A \textbf{81}, 062129 (2010)] on the DTQW with position measurements. We show that the position measurements per each step with probability $p \sim 1/n^\beta$ can be evaluated, where $n$ is the final time and $… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…We should remark that a relation between CTQW and DTQW on the infinite line is discussed in [15]. We also see more detailed discussion on the relations with respect to its weak limit theorems in [8]. In the case of CTQW determined by graph Laplacian on P n+2 [5], the time averaged distribution is almost the same as the uniform distribution.…”
Section: Resultsmentioning
confidence: 95%
“…We should remark that a relation between CTQW and DTQW on the infinite line is discussed in [15]. We also see more detailed discussion on the relations with respect to its weak limit theorems in [8]. In the case of CTQW determined by graph Laplacian on P n+2 [5], the time averaged distribution is almost the same as the uniform distribution.…”
Section: Resultsmentioning
confidence: 95%
“…In this section, we will see the relationship between the continuous time quantum walk (CTQW), which will be defined in the following subsection, and the DTQW according to Ref. [17].…”
Section: Connection To Continuous Time Quantum Walkmentioning
confidence: 99%
“…However it is believed that there are no non-trivial representations of the present distribution of QWs by that of past time like Markov chain [22]. QWs are applied to various study fields, for example, a problem of searching marked elements on graphs [6], [9], [10], [11], fundamental physics [13], [14], the limit theorems for its statistical behaviors [15], [16], spectral analysis [19], [20], and photon synthesis [17]. In [6], Szegedy walk was formulated as a natural quantization of reversible Marcov chains, and Szegedy showed that in most cases the quantized walk hits the marked set within the square root of the classical hitting time.…”
Section: Background and Notationmentioning
confidence: 99%